Motivation of Legislators and Political Will. (3rd March 2020) - Thompson, Gabriela; Staddon, Anthony; Stapenhurst, Rick
Abstract : That legislative oversight is an important determinant of corruption is well recognized, as is the fact that parliamentary oversight tools often have limited success both in holding governments to account and reducing corruption. Therefore, legislative oversight tools and mechanisms are a necessary but insufficient condition for effective oversight; rather, legislators must also have the political will to apply them effectively. Since legislators are charged with conducting oversight, it is argued here that understanding the motivation of legislators in the exercise of oversight will help to identify the mechanisms by which effective oversight can be sustained. The concept of political will is generally taken for granted and its meaning rarely made explicit. Nevertheless, the term continues to be used in everyday language, propagating the multiple, and often unfounded, assumptions it conjures. In terms of the battle against corruption, for example, it is claimed that a lack of political will is the perpetrator of poorly performing ethics and anticorruption initiatives. The authors, therefore, in understanding political will as a key motivator in the effective implementation of regulatory measures, seek to identify the conditions necessary to foster and maintain it among legislators based on a combination of theory and interview data.